2008
DOI: 10.1073/pnas.0802785105
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PI3K/Akt and MAPK pathways regulates Myc-mediated transcription by phosphorylating and promoting the degradation of Mad1

Abstract: Mad1, a member of the Myc/Max/Mad family, suppresses Mycmediated transcriptional activity by competing with Myc for heterodimerization with its obligatory partner, Max. The expression of Mad1 suppresses Myc-mediated cell proliferation and transformation. The levels of Mad1 protein are generally low in many human cancers, and Mad1 protein has a very short half-life. However, the mechanism that regulates the turnover of Mad1 protein is poorly understood. In this study, we showed that Mad1 is a substrate of p90 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(173 citation statements)
references
References 24 publications
6
165
0
2
Order By: Relevance
“…Similar to previous findings that Akt promotes pluripotency through the regulation and/or stabilization of Oct4, Sox2 and cMyc, in this study we observed that Akt-NLS also showed increased protein levels of reprogramming factors either similar or even more compared to wild type Akt. [38][39][40] However, Akt-NLS markedly differed from wild type Akt in the transcriptional ability of the reprogramming factors. While Akt-WT upregulated the mRNA levels of Oct4, Sox2, cMyc and Nanog drastically Akt-NLS showed no increased expression except for cMyc mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous findings that Akt promotes pluripotency through the regulation and/or stabilization of Oct4, Sox2 and cMyc, in this study we observed that Akt-NLS also showed increased protein levels of reprogramming factors either similar or even more compared to wild type Akt. [38][39][40] However, Akt-NLS markedly differed from wild type Akt in the transcriptional ability of the reprogramming factors. While Akt-WT upregulated the mRNA levels of Oct4, Sox2, cMyc and Nanog drastically Akt-NLS showed no increased expression except for cMyc mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies suggested the involvement of the MYC oncogene, which is downstream of the PI3K/mTOR pathway [31]. First, an unbiased screen showed that MYC conferred resistance to BEZ235 in the human mammary epithelial cell (HMEC) line MCF-10A, and that BEZ235-resistant human cell lines had higher c-MYC gene copy number compared to their sensitive counterparts [32].…”
Section: 4 + Bez235 In Vivomentioning
confidence: 99%
“…forms heterodimers with MAX that sequentially access transcriptional sites in a cell proliferation direction (Zhu et al 2008, Ni et al 2013; (3) AR induces dissociation of repressor transcription factor 7-like 2 (TCF7L2) from the pioneer transcription factor of AR, FOXA1, promoting AR target gene MYC transcription with mitogenic action (Ni et al 2013). There is a positive feed-forward loop involving MYC in the regulation of androgendependent transcription in ER-negative HER2-positive BC subtype; (4) AR induces ErbB2 expression, which activates ERK.…”
Section: :10mentioning
confidence: 99%